MASHSHA’IYAH: MAZHAB AWAL FILSAFAT ISLAM - Hasan Bakti (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Abstract: The development of Islam in the golden age was certainly spotted by philosophy (i.e. islamic philosophy), besides having been marked by political and economic progress as well as the advance of sciences in all fields. The advance of Islamic philosophy was marked by the emergence of various thoughts called as schools of Islamic philosophy, like Masysya'iyah (Peripatesism), Isyraqiyyah (Illuminasionism), and 'Irfaniyyah (Gnosticism). The Peripatic school is distinctly characterized by its argumentative and rational emphasis, and its use of Aristotelian logic through a reliable verification. This more applicable method has accordingly made the school get more support, from either its quantity or quality, than other two schools, i.e. Isyraqiyyah and ‘Irfaniyah/Gnosticism. Abstrak: Perkembangan Islam pada zaman keemasan, selain ditandai dengan kemajuan politik dan ekonomi, juga ditandai dengan perkembangan ilmu pe¬ngetahuan dalam semua bidang, termasuk dalam bidang filsafat Islam. Kemajuan filsafat Islam ini ditandai dengan bermunculan berbagai corak pemikiran yang juga disebut dengan mazhab filsafat Islam, seperti Mashsha’iyah (Peripatesisme), Isyrāqiyyah (Illuminasionisme), dan ‘Irfāniyyah (Gnosisme). Ciri khas mazhab peripatesis ialah semangatnya yang rasional argumentatif, menggunakan logika Aristoteles dengan pembuktian yang teruji dan rasional. Cara kerja yang lebih aplikatif ini membuat mazhab peripatesis lebih mendapat dukungan yang lebih banyak secara kuantitas dan kualitas dibanding dua mazhab lainnya, yaitu Isyrāqiyyah dan Gnosisme.